A prospective cohort study assessing the clinical utility of the Cottle maneuver in nasal septal surgery - James P. Bonaparte; Ross Campbell (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background A nasal septal deviation can have a significant detrimental effect on a patient’s quality of life. Nasal valve collapse (NVC) often co-exists with a septal deviation. The Cottle maneuver is one of the most common methods to diagnose NVC; however, no study has assessed the efficacy of this physical exam finding. This study tests the hypothesis that patients with nasal obstruction due to a septal deviation with a negative pre-operative Cottle maneuver will demonstrate a greater improvement in their Nasal Obstruction Symptom Evaluation (NOSE) score, compared to patients who demonstrate a positive pre-operative Cottle maneuver, when assessed at 12 months following a septoplasty with turbinate diathermy. Methods This was a prospective Cohort Study. The population was 141 patients with nasal obstruction due to a septal deviation with or without nasal valve collapse, excluding patients with bilateral complete nasal valve collapse. Patients were placed in cohorts according to the results of the Cottle maneuver (positive or negative). A NOSE questionnaire was administered at baseline and 12-months after a septoplasty with turbinate diathermy. Non-adjusted NOSE scores were used (score out of 20). An ANOVA was used to compare if there was a difference in outcomes between patient cohorts. Results One hundred and forty-one patients completed 12-month follow-up with 71.5% of patients demonstrating a positive Cottle maneuver at baseline. The mean (95% C.I.) difference in NOSE score at 12 months between patients with a positive Cottle versus a negative Cottle was 0.18 (− 1.6 to 1.92; p = 0.38). Conclusion In a univariate, single surgeon study, a positive Cottle Maneuver does not appear to influence outcomes in the described patient population compared to those with a negative Cottle Maneuver when undergoing a septoplasty.